Mining and its environmental impact - Hester, R. E.; Harrison, Roy M., 1948- (Royal Society of Chemistry, 1994)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. This first Issue in the series contains nine articles written by leading British and American experts from the mining industry, regulatory authorities, and academia, and incorporates the latest research. Following an introductory overview of many of the issues of current concern to the field, the book deals with a wide variety of topics, ranging from the environmental impact of gold mining in the Brazilian Amazon, through the issues relevant to coal mining, vegetative and other remediation strategies and procedures and water pollution, to a thorough analysis of environmental management and policy initiatives. The issues raised in Mining and its Environmental Impact may point the way to future solutions to the economic, technological and environmental problems associated with mining in all its aspects and make this volume key reading for practitioners and researchers in the field, as well as for environmentalists generally.
Keywords: Mineral industries -- Environmental aspects.; Hazardous waste site remediation.; Coal mines and mining -- Environmental aspects.; elektronické knihy; electronic books